CRISPR Screens in Toxicology Research: An Overview. Issue 5 (27th May 2021) - Sobh, Amin; Russo, Max; Vulpe, Christopher D.
Abstract: The use of genome editing tools is expanding our understanding of various human diseases by providing insight into gene–disease interactions. Despite the recognized role of toxicants in the development of human health issues and conditions, there is currently limited characterization of their mechanisms of action, and the application of CRISPR‐based genome editing to the study of toxicants could help in the identification of novel gene–environment interactions. CRISPR‐based functional screens enable identification of cellular mechanisms fundamental for response and susceptibility to a given toxicant. The aim of this review is to inform future directions in the application of CRISPR technologies in toxicological studies. We review and compare different types of CRISPR‐based methods including pooled, anchored, combinatorial, and perturb‐sequencing screens in vitro, in addition to pooled screenings in model organisms. © 2021 Wiley Periodicals LLC.